Inverse Modeling Using Taylor Expansion Approach and Jacobi Matrix on Magnetic Data (Dyke/Magma Intrusion Cases) - Agus Suprianto; Wahyudi Wahyudi; Wiwit Suryanto; Ari Setiawan; Aryono Adhi; Nurul Priyantari; Supriyadi Supriyadi; Agus Subekti (Universitas Negeri Semarang, 2019)
The mathematical modelling of geological structures, i.e. magma intrusion or dyke, has been done,Â based on magnetic data with inversion techniques using MatLab. The magnetic equation is a non-linear equation, and completion is done using a linear approach to non-linear mathematical models of magnetic data using the Taylor expansion approach and Jacobi Matrix. The first step of this research is to make synthetic data forward modelling from the magnetic equation of magma intrusion or dyke cases without errors, and the next stepping then add errors to the data. The next step is to do an inversion to get the parameters sought, i.e. depth and angle of the magma intrusion, by giving initial guesses, and then re-correct iteratively until convergent results are obtained. Finally, parameters of slope dyke or thin magma intrusion and its depth can be determined. The results obtained indicate that this technique can be used to get physical parameters sought from magnetic data for simple geological cases, i.e. dyke and magma intrusion.